2017
DOI: 10.1590/s1518-8787.2017051006051
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with human brucellosis in livestock professionals

Abstract: OBJECTIVE The objective of this study is to estimate the seroprevalence of human brucellosis in livestock professionals and analyze the factors associated with brucellosis focusing on sociodemographic variables and the variables of knowledge and practices related to the characteristics of the activities carried out in livestock.METHODS This is a cross-sectional seroepidemiological study with a population of 131 workers of butchers, slaughter rooms, and slaughterhouse and 192 breeders sampled randomly in Namibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
1
30
0
3
Order By: Relevance
“…Respecto a este último factor, el consumo de lácteos no pasteurizados continúa siendo una de las principales causas de infección (Swai & Schooman 2009;Yoo et al 2009;Cavalcanti et al 2015;Mufinda et al 2017;Acharya et al 2018). A pesar de que, en el área de estudio, la práctica de consumir productos lácteos sin pasteurizar es muy frecuente y es un importante factor de riesgo, se considera importante hacer notar que el consumo de leche, que se esperaba fuera un factor de riesgo, no lo es (Cavalcanti et al 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Respecto a este último factor, el consumo de lácteos no pasteurizados continúa siendo una de las principales causas de infección (Swai & Schooman 2009;Yoo et al 2009;Cavalcanti et al 2015;Mufinda et al 2017;Acharya et al 2018). A pesar de que, en el área de estudio, la práctica de consumir productos lácteos sin pasteurizar es muy frecuente y es un importante factor de riesgo, se considera importante hacer notar que el consumo de leche, que se esperaba fuera un factor de riesgo, no lo es (Cavalcanti et al 2015).…”
Section: Discussionunclassified
“…Al respecto, existe amplia evidencia de que las causas más comunes de infección han sido las condiciones laborales relacionadas con los profesionales de ganado expuestos (veterinarios, trabajadores de mataderos y criadores de animales) y el consumo de productos infectados (carne, leche y productos lácteos) (Swai & Schooman 2009;Yoo et al 2009;Mufinda et al 2017;Acharya et al 2018).…”
Section: Introductionunclassified
“…In the study designed by [33] in Karnataka, India noticed that the prevalence of brucellosis by Rose Bengal plate test (RBPT) was 6.38 %. In Angola, namibe province, [22] mentioned that the general weighted prevalence of brucellosis was 15.6% from a population of 131 workers of butchers, slaughter rooms, slaughterhouse, and 192 breeders sampled randomly.Also,table1shows that the female are more exposed to infection with Brucella, the rate of infection in female was 13/ 134 (9.7%), compared with the rate of infection in males were 11/146 ( 7.5%).This result was compatible with [34] in Pakistan, who indicated that the prevalence of brucellosis in females (25.58%), while in males (10.18%). In another hand, [32] noticed that the prevalence of brucellosis in males (11.6%).…”
Section: Prevalence Of Human Brucellosis In Erbil Governorate Accordimentioning
confidence: 99%
“…Rose Bengal Test (RBT) is timely diagnostic tool, simple, high sensitivity, easy, cheap, and accurate. Rapid slide-type agglutination assay performed with a stained Brucella abortus suspension at pH 3.6-3.7 and plain serum, which was designed originally for screening use in veterinary medicine, but nowadays is widely used for identifying human brucellosis [21,22].Therefore, the objectives of this work were to monitoring the human brucellosis according to gender, age, and residence (Rural or Urban), by application of RBT in Erbil Governorate ,and to determine the relationship between occurrence of brucellosis in humans with months during the period of study . Also high light on the hazard of brucellosis help the peoples to understand the different ways of infection with Brucella in order to protect themselves from this prevalent disease.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, brucellosis can inflict high economic costs in terms of medical tests, treatment, and worker absence, which makes it also a considerable social problem particularly in developing nations. It also induces fear in the community, which can negatively affect the global trade of meat, milk, and their products (Mufinda et al, 2017;Raghava et al, 2017).…”
Section: Introductionmentioning
confidence: 99%